THE IMPORTANCE OF STIM-HOTS AND CRITICAL THINKING SKILL IN DISRUPTION ERA - Riky Rivaldi Pratama; Rizky Ardhia Pramesti (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
Enhancing the quality in life is needed in this globalization era. The development in Science and Technology makes all the countries maximizing all the resources that they have to survive in this Era. Science Education has a urgent role in developing Science and Technology. Science education that appropriate with indictment in 21th century is a education that consider in HOTS ( High Order Thinking Skill ). Critical thinking skill is one of skill in HOTS. It is essensial and effective in all the aspect of life. Therefore, critical thinking skill must educated  since early. The learning model that can be used to enhancing the critical thinking skill is STIM-HOTS. It is make student think critically, because they  will build the scheme from initial knowledge with the new content. The purpose are, the student can be a problem solver and they have a high productivity.